Kajian Teologis Peranan Gereja Dalam Memerdekakan Masyarakat Dari Kemiskinan: A Theological Study on the Role of the Church in Liberating Society from Poverty - Yefri Edowai (Journal of Religious and Socio-Cultural, 2024)
Poverty is a reality that exists within society and is an unavoidable aspect of human life. The Bible explicitly discusses poverty as a constant presence in human existence. The Church, in its theological and ecclesiological functions, serves as a medium for proclaiming the Gospel, with its target being the world in which society resides. In a pejorative sense, the Church represents Christianity, and the foundation of Christianity is love, which must be enacted in society. Therefore, the Church cannot detach itself from the issues present in human life, as it endeavors to realize the social dimension of Christian faith. The Church's efforts to liberate society from poverty are carried out through diaconal services, a form of ministry that reflects the compassion of the early Church, serving as a standard for measuring the Christianity of believers. The egalitarian principle, which asserts that every individual, regardless of background, has the same opportunity for equality and to reduce societal disparities, serves as a guiding principle for the Church in conducting social services aimed at alleviating poverty. The Church is considered the most important institution in the world as a gift from God and a vessel to display His glory. Thus, efforts to liberate society from poverty are viewed as the Church's duty and responsibility. The research method employed is qualitative, with a text analysis approach as the primary research method. The findings indicate that if the Church fulfills its role according to biblical standards, both theologically and ecclesiologically, it can effectively liberate society from poverty through well-targeted diaconal strategies aimed at those who genuinely need assistance and are ready to be empowered. Kemiskinan merupakan realita yang ada dalam masyarakat dan tidak dapat di hindari dari kehidupan umat manusia. Alkitab secara jelas membahas tentang kemiskinan yang selalu ada di dalam kehidupan umat manusia. Gereja dalam fungsi teologis dan eklesiologis merupakan sarana pemberitaan Injil dan sasarannya adalah dunia dimana masyarakat berada.Gereja dalam istilah peyoratif mewakili kekristenan dan landasan dari kekristenan adalah kasih yang di implikasikan dalam kehidupan di tengah-tengah masyarakat, sehingga gereja tidak dapat terlepas dari masalah-masalah yang ada dalam kehidupan manusia sebagai upaya merealisasikan dimensi social iman Kristen. Upaya gereja untuk memerdekakan masyarakat dari kemiskinan melalui pelayanan diakonia suatu bentuk pelayanan yang mengaitkan belas kasihan gereja mula-mula sebagai standar mengukur kekristenan orang percaya. Prinsip egalitarian dimana setiap individu terlepas dari latar belakang apapun memilki kesempatan yang sama untuk kesetaraan dan mengurangi kesenjangan dalam masyarakat menjadi acuan dalam gereja menjalankan pelayanan social dalam konteks mengentaskan kemiskinan. Gereja merupakan lembaga terpenting di dunia sebagai pemberian Tuhan dan bejana untuk memperlihatkan keagungan Tuhan sehingga upaya dalam memerdekakan masyarakat dari kemiskinan menjadi tugas dan tanggung jawab gereja. Metode penelitian yang di gunakan adalah kualitatif dengan pendekatan analisis teks sebagai metode penelitian utama. Hasil penelitian menunjukkan apabila gereja menjalankan peranannya sesuai standar alkitab baik secara teologis dan eklesiologis maka akan mampu memerdekakan masyarakat dari kemiskinan dengan strategi tepat dalam menjalankan diakonia dan arah sasaran tepat pada orang-orang yang memang memerlukan pertolongan serta siap untuk di berdayakan.